Acoustic ecology of dolphins of the genus Sotalia (Cetartiodactyla, Delphinidae) and of the newly described Araguaian boto Inia araguaiaensis (Cetartiodactyla, Iniidae) - SANTOS, Gabriel Melo Alves dos (Universidade Federal do Pará, 2018)
Sensory systems are vital for animals to obtain information about their surroundings. Information can be gathered via visual, chemical, electrical, tactile and acoustic cues. These cues are used in several ecological contexts including foraging, competition, defense, social interactions (e.g. courtship behavior), and to indicate a condition, emotional or reproductive state or identity of the signal emitter. For aquatic mammals, sound is the most important mechanism of communication. Light attenuates rapidly with depth in aquatic environments limiting visual communication. In contrast, sound has low attenuation in water and it travels about five times faster in water than in air, making a very efficient way to communicate underwater. Therefore, sound is a fundamental aspect of cetacean biology, as these animals rely on acoustic signals for communication, navigation and location of prey. The genus Sotalia consist of two species that inhabit contrasting habitats. The Guiana dolphin (Sotalia guianensis) inhabits the coastal waters from Nicaragua to Southern Brazil, and the tucuxi (Sotalia fluviatilis) is confined to the main tributaries of the Amazon Basin. Meanwhile, river dolphins of the genus Inia - commonly known as botos - are found exclusively in the Amazon, Orinoco, and Tocantins River Basins. With their conservation status of both genera as data deficient there is great demand for information on their biology. As a key factor on cetacean biology acoustics can provide us with a richness of information and used as a tool to acquire data on habitat use, population numbers and behavior. However, in order to do so, first one needs to know the species vocal repertoire in detail and be able to differentiate those using acoustic methods. Thus, here we present the first distributionwide analysis of the vocal repertoire of Sotalia dolphins and diversity and geographical patterns of their whistles. In addition, we present the first description of the vocal repertoire of Inia araguaiaensis focusing on repertoire diversity and structure. The whistle repertoire of both Sotalia species is highly structured, with populations of the riverine species showing a less diverse whistle repertoire than the populations of the coastal species. The highly structured repertoire is likely due to the small home ranges and low gene flow among populations. Differences in the richness of the acoustic repertoire between both species, may be due to a combination of socioecological and evolutionary factors. We also provide the first description of the Araguaian boto (Inia araguaiensis) acoustic behavior and showed that they have a rich acoustic repertoire consisting of whistles and primarily pulsed calls. While whistles were produced rarely, a specific type of call, the short two-component calls were the most common signal emitted during the study. These calls were similar in acoustic structure to those produced by orcas (Orcinus orca) and pilot whales (Globicephala sp.). Because of the context at which these signals were produced, we hypothesize that they possibly play a role in mother-calf communication. Sotalia and Inia can be acoustically distinguished based on their social sounds, as the former has a repertoire based on whistles and the latter based on pulsative calls. With the low emission rate of whistles by Inia, so chances of misidentification are low. Thus, sounds of both genera can be used to distinguish them from one another during passive acoustic monitoring and serve as proxies for species presence in studies of distribution, habitat use, and abundance.